Current status of the environmental monitoring database on the accident at Fukushima Daiichi Nuclear Power Plant. (18th August 2021) - Seki, Akiyuki; Saito, Kimiaki; Takemiya, Hiroshi
Abstract: An enormous amount of environmental monitoring data has been acquired by various organisations for the evaluation and implementation of countermeasures to mitigate the effects of the accident at the Fukushima Daiichi Nuclear Power Plant. However, it is difficult to collate, compare, and analyse this data because it was published in different formats at different sites according to the respective objectives of the publishing organisations. Moreover, these organisations have been accumulating data in large volumes for over nine years after the accident. We established procedures to collect this data, convert them into a unified format, classify them according to categories, and make the data accessible on a web-based database system. The database contains environmental monitoring data on air dose rates, ground deposition densities, and concentrations in various environmental samples such as soil, water, and food. This data is being provided not only in numerical format for quantitative analysis but also as distribution maps and time-series graphs for visual understanding. The database system enabled us to spatially and temporally compare large volumes of monitoring data. By using the database functions, characteristics of some representative data in the database was clarified.